Role and Clinical Application of Metagenomic Next-Generation Sequencing in Immunocompromised Patients With Acute Respiratory Failure During Veno-Venous Extracorporeal Membrane Oxygenation - Zhao, Yang-Chao; Ding, Yan-Zhong; Zhao, Xi; Fu, Guo-Wei; Huang, Ming-Jun; Li, Xing-Xing; Sun, Qian-Qian; Kan, Ya-Bai; Li, Jun; Wang, Shi-Lei; Ma, Wen-Tao; Xu, Qin-Fu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: There are few studies of metagenomic next-generation sequencing (mNGS) in immunocompromised patients assisted by veno-venous extracorporeal membrane oxygenation (vv-ECMO). The present study is aimed to investigate the pathogen detected effect and clinical therapy value of mNGS technologies in immunocompromised patients assisted by vv-ECMO. Methods: Our study retrospectively enrolled 46 immunocompromised patients supported by vv-ECMO from Jan 2017 to June 2021 at the First Affiliated Hospital of Zhengzhou University respectively. Patients were divided into deterioration group (Group D) (n=31) and improvement group (Group I) (n=15) according to their outcomes. Baseline characteristics and etiological data of patients during hospitalization of 2 groups were compared. The pathogens detected by mNGS and antibiotic regimens guided by mNGS in immunocompromised patients assisted by vv-ECMO were analyzed. Results: Compared with Group I, the deterioration patients showed higher percentage of COPD (32.3% vs 6.7%, p<0.01)) and were significantly older (47.77±16.72 years vs 32±15.05 years, p<0.01). Within 48 hours of ECMO assisted, the consistency of the samples detected by traditional culture and mNGS at the same time was good (traditional culture vs. mNGS detection, the positive rate of bronchoalveolar lavage fluid (BALF) culture: 26.1% vs. 30.4%; the positive rate of blood sample culture: 12.2% vs. 12.2%, p>0.05). However, mNGS detected far more pathogen species and strains than conventional culture (30 strains vs. 78 strains, p<0.01), the most popular pathogen was Klebsiella pneumoniae. Parts of patients had their antibiotic treatment adjustments, and the improvement patients showed less usage of broad-spectrum antibiotics. Conclusions: mNGS may play an relatively important role in detecting mixed pathogens and personalized antibiotic treatment in immunocompromised patients assisted by vv-ECMO.